Physical properties and in situ geoacoustic properties of seafloor surface sediments in the East China Sea - Wang, Jingqiang; Kan, Guangming; Li, Guanbao; Meng, Xiangmei; Zhang, Linqing; Chen, Mujun; Liu, Chenguang; Liu, Baohua (Frontiers in Marine Science, 2023)
Seafloor sediment acoustics is a burgeoning field of marine scientific research. In situ measurement technique is a key technique for investigating sediment acoustic properties. Establishing a correlation between in situ acoustic parameters and physical parameters is of great scientific significance for advancing the theory of seafloor acoustics. This study employed an in situ sediment acoustic measurement system to measure the sound speed and attenuation of various types of sediment, such as sand, silty sand, silty clay, and clayey silt. The results showed that in situ sound speed and attenuation were strongly curvilinear correlated with physical properties, such as wet bulk density, porosity, and mean grain size. Empirical regression relationships between in situ acoustic properties and physical properties were derived. These findings supplement the in situ measurement data of acoustic properties of seafloor sediments, compensate for the lack of an empirical relationship of in situ attenuation in previous studies, and broaden the predicting theory and method of the acoustic properties of seafloor sediments.